Effect of graded levels of NPK on growth and leaf nutrient content of apple (Malus Ã— domestica) nursery plants - CHAUHAN, PRIYANKA; SHARMA, NAVEEN C; CHANDEL, J S; KUMAR, PRAMOD; SHARMA, UDAY (The Indian Journal of Agricultural Sciences, 2022)
An experiment was conducted during 2017â€“18 to study the effect of different N, P and K doses on vegetative growth and leaf nutrient content of apple nursery plants of cultivar Starking Delicious and to find out the optimum dose of nutrients for production of healthy planting material for Merton 793 rootstock. The experiment was laid out in a randomized block design comprising 12 combinations of N, P2O5 and K2O {3 levels of N (12, 15 and 18 g/m2 nursery bed), 2 levels of P (3 and 6 g/m2 nursery bed) and 2 levels of K (4.5 and 9 g/m2 nursery bed)}, Jeevamrut and control. The results revealed that maximum linear growth of plant, number of leaves, leaf area, length of main root, total root length, fresh and dry weight of roots, leaf P, Mg and Ca contents were recorded in the plants fertilized with NPK @18:6:4.5 g/m2. However, radial growth of plant, internodal length, fresh and dry weight of shoots, total biomass, leaf N and K were highest in the plants treated with NPK @18:6:9 g/m2 nursery bed. NPK @18:6:4.5 g/m2 nursery bed and NPK @18:6:9 g/m2 nursery bed were found statistically at par with each other with respect to plant growth and leaf nutrients. Thus, nursery bed with 18.0 g N, 6.0 g P and 4.5 g K per m2 was found most suitable for production of quality nursery plants of apple plantlets on Merton 793 clonal rootstock.